Deep-sea cnidarians of Northwest Africa: Distribution patterns - Ramil, Francisco; Matos-Pita, Susana Soto de; Gil, Marta; Castillo, Sara; Ramos, Ana (2015)
Cnidarians are one of the most relevant phylum in deep-waters, where Scleractinia, Alcyonacea and Antipatharia may build three-dimensional habitats which host some of the most biodiverse and vulnerable marine ecosystems (‘hot-spots’) along the continental margins. Although ancient expeditions recorded the existence of Lophelia pertusa on the Moroccan, Western Saharan and Mauritanian slopes, the distribution of this cold-water coral and other related vulnerable species in Northwest African is currently unknown. The intensive benthic sampling program developed in the CCLME region from 2002 to 2012 within the framework of the EcoAfrik and FAO EAF-Nansen projects, has allowed to obtain a first insight of the biodiversity and distribution patterns of the cnidarians along the deep-shelf and slope of Northwest Africa. This work analyzes the quantitative data of nine cnidarian taxa (Hydrozoa, Scyphozoa, Alcyonacea, Pennatulacea, Antipatharia, Ceriantharia, Zoantharia, Actiniaria and Scleractinia) collected at 908 trawling stations, carried out between 100 and 1865-m depth, during the 11 research surveys developed onboard R/V Dr. Fridtjof Nansen and R/V Vizconde de Eza in the region. The highest diverse taxa are undoubtedly Hydrozoa (more than 100 species), followed by Alcyonacea and Actiniaria; Zoantharia, Ceriantharia and Scyphozoa showed the lowest values. Our results mainly evidenced that the Saharan and South Moroccan waters were the highest diverse areas, followed by Cape Verde Islands. Diversity values were four times higher northern Cape Blanc than in the tropical area, being Hydrozoa and Alcyonacea the main contributors to the cnidarian diversity in the northern area. Only Actiniaria was the most diverse taxon in the southern part, exhibiting together Zoantharia high biomass values. Antipatharia (black corals) show some relevance only in Cape Verdean and Saharan slopes. The intensive sampling program developed in Northwest Africa will allow the identification and location of areas hosting vulnerable cnidarians, ...